ANALISIS TINGKAT KEPUASAN PENUMPANG ATAS KUALITAS PELAYANAN SHUTTLE & TRAVEL PT.CIPAGANTI CITRA GRAHA OTOJASA SEMARANG - Kalista, Cikita Amalia; Lubis, Nawazirul; Listyorini, Sari (Jurnal Ilmu Administrasi Bisnis, 2012)
The development of business transportation is increasing rapidly. It means the company to compete in providing the best service to achieve the satisfaction of passangers. The research was carried out at PT. Cipaganti Citra Graha Otojasa Semarang with object Shuttle & Travel. From the data of visitors Cipaganti been no complaints of visitors related to vehicles, facilities, and services. This study aims to determine the level of passenger satisfaction for the quality of service Shuttle & Travel Cipaganti, consisting of attributes reliability, responsiveness, assurance, empathy, and tangibles. Type the study is a descriptive analytic. The data used in this study is primary data obtained using data collection instruments such as questionnaires and guiding Question. The population in this study were all passengers Shuttle & Travel Semarang, the sample of 100 respondents who used the technique purposive sampling. Analysis of the data used in this study is the Importance and Performance Analysis (Analysis of Importance and Performance / Satisfaction). Based on the Importance and Performance Analysis, it could be concluded that the average total for the dimensions of service quality are included in the category compatible. This shows performance service of Cipaganti that have been in compatible with the expectation of passengers. Advice can be given to the company is to improve service performance Cipaganti deemed important by visitors but still received less attention than the company as a driver order, speed of service, ease of contacting officers, and officers in communication skills.